Optimization of nutrient management improves productivity, quality and sustainability of albino tea cultivar Baiye-1 - Zhu, Yun; Ma, Lifeng; Geng, Saipan; Ruan, Jianyun (Frontiers in Plant Science, 2024)
Proper nutrient management is crucially important to the sustainable development of tea production. Compared to normal green-leaf cultivars, albino tea cultivars produce green tea of superior quality characterized by high contents of amino acids as a result of the hydrolysis of chloroplast proteins at albinism. However, the advantage of albino tea cultivars was offset by inferior growth and yield performance because of low contents of chlorophylls and limited photosynthesis capacity. Our understanding about the nutrition characteristics of albino tea cultivars was very limited. A four-year field experiment was conducted to develop proper nutrient management for Baiye-1 to overcome its weakness of low productivity without a tradeoff in tea quality and environmental risks. The nutrient management schemes were formulated by optimizing the rate and ratio of nitrogen (N), phosphorus, potassium and magnesium together with substitution of chemical fertilizers with organic manures. The total amounts of nutrients in the optimized schemes were reduced by 25% compared to the local farmers’ practice (FP). Results showed that optimized rates and ratio of nutrients together with partial substitution of chemical fertilizers with rapeseed cake manure more considerably improved albino tea yield, the contents of free amino acids, total polyphenol and catechins relative to FP. Partial substitution of chemical fertilizers with commercial livestock manure decreased tea quality, which was likely caused by a dilution effect of increasing tea yield and decreasing N status of tea plants. Full organic substitution of chemical fertilizers by rapeseed cake manure improved tea yield and quality but had relatively low agronomic efficiency and profit. The effect of optimized nutrient management schemes was associated with the improvement of nutritional status in tea plants. The present work demonstrated that the optimization of nutrient management considerably improved albino tea yield, quality and profit while decreased the application rate of fertilizers and the intensity of greenhouse gas emissions.